The Effectiveness of the Use of Urban Village Funds in Infrastructure Development: A Study in Kemenangan Tani Village, Medan Tuntungan - Grace Angelia Paulina Dakhi (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
The allocation of village funds is intended to accelerate the development of basic infrastructure at the local level. However, in practice, the effectiveness of fund utilization is often questioned, particularly regarding the alignment between planning, implementation, and the resulting outcomes. This study aims to analyze the extent to which the utilization of village funds in Kemenangan Tani Subdistrict, Medan Tuntungan District, can be considered effective in supporting infrastructure development. The primary issue addressed in this study is whether the realization of fund utilization has significantly contributed to the improvement of public facilities and infrastructure within the community. This research employs a descriptive qualitative approach using secondary data, including budget allocation and realization reports from 2022 to 2024, as well as documentation of existing infrastructure conditions. The findings indicate that although the rate of budget realization is relatively high, not all infrastructure projects have generated direct and tangible benefits for local residents. These results suggest the need to improve planning mechanisms and evaluation processes to ensure that the allocation of funds is more targeted and effective in achieving its intended development objectives.